Analisis Kompetensi dalam Meningkatkan Kinerja Pegawai pada Biro Pemerintahan dan Otonomi Daerah Provinsi Sulawesi Tenggara - Khariq Darmawan; Nofal Supriaddin; Muh Nur (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to determine competence in improving employee performance in government bureaus and regional autonomy of Southeast Sulawesi Province. The method used in this study is qualitative descriptive method. The types of data used in this study are quantitative and qualitative data. The methods carried out in collecting data in this study are interviews and documentation. The informants in this study were 4 regional apparatus ranks. Data analysis techniques are data collection, data reduction, data presentation, and conclusions. The results of the data analysis show that the competence of employees at the Bureau of Government and Regional Autonomy of Southeast Sulawesi Province is good, which is assessed in terms of knowledge, expertise and attitudes is good and able to improve employee performance. The performance of employees at the Bureau of Government and Regional Autonomy is assessed by quality, quantity, punctuality, effectiveness and attendance is good. The competence of employees in improving the performance of employees of the Bureau of Government and Regional Autonomy is good. Improving employee competence through training and education, and development, workshops, seminars, collaboration with educational institutions, and the use of educational technology such as e-learning for distance learning